2023
DOI: 10.1007/s11657-023-01361-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in UK fracture liaison service consultation conduct and content before and during the COVID pandemic: results from the iFraP-D UK survey

Laurna Bullock,
Sittana Abdelmagid,
Jane Fleming
et al.

Abstract: Summary We conducted a survey of FLSs’ consultation conduct and content which identified marked variation in whether FLS HCPs discussed osteoporosis medicine with patients. A review of service pro formas showed more content related to ‘investigating’ and ‘intervening’ than to ‘informing’. We propose an expanded FLS typology and model FLS pro forma. Purpose To investigate the nature of direct patient contact in fracture liai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…We hypothesize that the iFraP intervention will improve patient ease in decision-making about osteoporosis medicines (by increasing the extent that the patient was informed and involved in the consultation), facilitate shared decision-making, increase informed medicine initiation and reduce levels of medicine discontinuation. A protocol outlining the studies that underpinned iFraP intervention development is published 20 , and the results of the development studies are also reported elsewhere 17,[21][22][23] .…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the iFraP intervention will improve patient ease in decision-making about osteoporosis medicines (by increasing the extent that the patient was informed and involved in the consultation), facilitate shared decision-making, increase informed medicine initiation and reduce levels of medicine discontinuation. A protocol outlining the studies that underpinned iFraP intervention development is published 20 , and the results of the development studies are also reported elsewhere 17,[21][22][23] .…”
Section: Background and Rationalementioning
confidence: 99%
“…Service provision varies across FLSs, with services ranging from operating a 'one-stop shop' model of care, meaning that, if appropriate, patients have a bone density scan (Dual-energy X-ray absorptiometry [DXA]), nurse assessment, drug treatment recommendation, and blood tests as part of one consultation. Other FLS models may not complete all components for all patients (for example, not all patients receive a DXA scan), or may split these components across multiple appointments, supported by different communication modalities (remote, face-to-face, letter) 22 .…”
Section: Trial Contextmentioning
confidence: 99%
“…This finding necessitated a national survey of FLS usual care to quantify the number of services which discuss osteoporosis medicines with patients, in which the iFraP intervention would be relevant. The iFraP national survey of FLS usual care found that more than a quarter of responding UK FLSs did not explain osteoporosis medicines with the patient [48]. This is important given that GPs' report lacking confidence, knowledge, and skills to discuss osteoporosis medicine.…”
Section: Implications For Ifrap Developmentmentioning
confidence: 99%